Perbandingan Metode MOORA dan SMART dalam Kelayakan Pemberian Kredit pada Calon Debitur Koperasi - Lenny Margaretta Huizen; Nurtriana Hidayati; Muhammad Basyier Ardima (AITI, 2023)
The Koperasi is a business entity whose activities are based on kinship. There are several types of Koperasi, including Savings and Loans Koperasi. Savings and Loans Koperasi is a type of Koperasi whose function is to serve members who are in it and who are not members to carry out savings or loan business services. Granting loans to prospective debtors, of course, must be with much consideration. The process for disbursing funds generally takes two working days. This is because several things must be analyzed regarding the feasibility of prospective debtors in receiving loan credit, ranging from salary, home ownership, how many loans are proposed, what is guaranteed, and other things that can be considered. The SMART method and the MOORA method are two of the existing methods in a decision support system. These two methods perform multi-attribute decision-making where each decision chooses the highest result in ranking several alternatives. The data taken is data from prospective debtors from December 2021-March 2022. The calculations between actual data and calculations of SMART and MOORA SPKs show that from the calculations with SMART, 69.072% have the same results as actual data, and 30.928% have different results from the actual data. In the MOORA method, 40.206% of data have the same as actual data, and 59.79%. have different results from actual data.